EPS Moderating the Influence of NPM and ROE on Stocks - Lusi Alfarenza; Acep Komara (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2026)
This study examines how stock prices in Indonesia’s mining sector are influenced by financial performance, particularly Net Profit Margin (NPM) and Return on Equity (ROE). The study tracks 17 carefully chosen companies listed on the IDX from 2022 to 2024 using Earnings Per Share (EPS) as a moderating variable, producing 51 observations. Statistical testing using Stata 17’s Moderated Regression Analysis (MRA). On the one hand, ROE significantly raises stock prices. Surprisingly, however, NPM exhibits a strong negative impact and pushes in the opposite direction. The information also demonstrates that EPS plays a crucial moderating role in effectively mitigating the relationship between NPM and market pricing. However, when examining ROE, this similar moderating impact vanishes. In the end, these observations provide investors and business executives attempting to identify the precise financial forces that shift shareholder value throughout Indonesia's unstable mining environment in recent years with a clearer road map. Keywords: EPS; NPM; ROE; Stock Price; Mining Sector